2015
DOI: 10.1007/s12098-015-1730-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Prognostic Factors and Mortality in Children with Esophageal Atresia

Abstract: Total mortality in newborns with EA was high; sepsis being the most frequent cause of death. The high total mortality was also caused by prematurity, delay in diagnosis, increased incidence of the aspiration pneumonia and shortage of qualified nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 23 publications
3
13
0
7
Order By: Relevance
“…This finding was consistent with other reports. [ 13 , 30 ] Another independent risk factor for mortality in the present study was respiratory failure, which was consistent with other findings. [ 4 , 26 ] Respiratory failure caused by gastric fluid reflux into the lungs could increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with other reports. [ 13 , 30 ] Another independent risk factor for mortality in the present study was respiratory failure, which was consistent with other findings. [ 4 , 26 ] Respiratory failure caused by gastric fluid reflux into the lungs could increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 93%
“…[ 4 , 26 ] Respiratory failure caused by gastric fluid reflux into the lungs could increase the risk of mortality. [ 6 , 30 ] A low birth weight has already been considered one of the substantial risk factors for mortality in many studies. [ 2 6 ] A birth weight less than 1500 g was considered one of the risk indicators in the prognostic classification system established by Spitz et al [ 15 ] A nationwide investigation performed in 2014 indicated that a birth weight less than 1500 g remains an independent predictor of mortality in infants with EA in the United States, and the survival rate in infants whose birth weight was greater than 1500 g was more than 92%.…”
Section: Discussionmentioning
confidence: 99%
“…The overall outcome of treatment of these patients was poor compared to the outcome in HICs . The poorer outcome in our setting as well as some other developing countries might be related to continuing barriers to care imposed by delayed presentation, inadequate facilities and general lack of funding at both personal and public levels. A closer look at our findings will show that mortality in this series was contributed mostly by conditions such as oesophageal atresia, intestinal atresia and abdominal wall defects where intensive care is critical to good outcome.…”
Section: Discussionmentioning
confidence: 62%
“…Похожую по дизайну научную работу опубликовали сербские авторы под руководством M. Vukadin в 2015 г. [31]. В исследование включили 60 новорожденных со средней массой тела при рождении 2660 г (1100-4140 г), средним сроком гестации 38 нед.…”
Section: развивающиеся страныunclassified
“…Летальность оказалась выше, чем в развитых странах, и составила 28,3 %. Причиной летального исхода в большинстве случаев был сепсис (p = 0,002), также на выживаемость оказали влияние хирургические осложнения (p = 0,003) [31].…”
Section: развивающиеся страныunclassified